2019
DOI: 10.1111/eea.12831
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐off between attraction to aggregation pheromones and repellent effects of spike lavender essential oil and its main constituent linalool in the flour beetle Tribolium confusum

Abstract: Essential oils of aromatic plants and their individual volatile components have been tested in pest management strategies for their toxic and often repellent effects on target insects. When evaluating their possible effects on crucial behaviours of the pest insects, the olfactory environment including intraspecific communication cues has to be considered. We used the flour beetle Tribolium confusum du Val (Coleoptera: Tenebrionidae), a common stored‐product pest, to investigate the influence of oil of spike la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…Five beetles in a stimulation tube were highly attractive to individual T. confusum , confirming earlier results [ 9 ] ( Figure 3 , p < 0.0001). When combining this attractive stimulus with the highly repulsive dose of 5 mg of the essential oil of V. globosa , attractiveness was lost ( p = 0.308).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Five beetles in a stimulation tube were highly attractive to individual T. confusum , confirming earlier results [ 9 ] ( Figure 3 , p < 0.0001). When combining this attractive stimulus with the highly repulsive dose of 5 mg of the essential oil of V. globosa , attractiveness was lost ( p = 0.308).…”
Section: Resultssupporting
confidence: 90%
“…Antennal detection, as well as repulsive behavioral responses of T. confusum, to the entire oil, to different degrees to its major components, anethole and caryophyllene, and their mixture were discovered. A similar repellent effect on T. confusum adults had been observed earlier with Lavandula spica essential oil and its main component linalool [9]. In addition to the repellent effect found in the present study, anethole also showed significant toxicity by fumigation against T. confusum and Sitophilus oryzae adults [28], as well as repellency to two Tribolium and two Sitophilus species [29].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations